The influence of social support on the physical exercise behavior of college students: The mediating role of self-efficacy - Zhang, Yan; Hasibagen,; Zhang, Chang (Frontiers in Psychology, 2022)
Abstract: Objectives: To study the influencing factors on college students’ physical exercise behavior and the mediating relationship of self-efficacy based on the theory of social support and self-efficacy; to provide theoretical support and practical guidance for college students engaging independently in physical exercise. Methods: A total of 1,440 college students from six universities in the Inner Mongolia Autonomous Region of China were selected as the research objects, and three scales (Self-Efficacy Scale, Social Support Scale, and Physical Exercise Rating Scale) were used to construct a structural equation model. Results: (1) A comprehensive sports facility environment is conducive to college students’ physical activities and that the emotional support of friends and family and the campus cultural atmosphere cannot be ignored. (2) Peer support has a direct impact on physical exercise behavior, family support and school support indirectly affect college students' physical exercise behavior, based on the intermediary role of self-efficacy. (3) According to the total effect, social support was ranked as school support (0.444), peer support (0.312), and family support (0.145). Conclusion: Social support not only directly affects physical exercise behavior but also indirectly affects physical exercise behavior based on the mediating effect of self-efficacy.